Pengaruh Pengawasan terhadap Disiplin Kerja Pegawai Negeri Sipil pada Kantor Sekretariat DPRD Kota Probolinggo - Novi Sri Sandyawati (Departement of Mathematics Education, 2021)
This study aims to determine the implementation of supervision regarding the level of discipline of Civil Servants and to find out how the influence of supervision on the discipline of civil servants at the secretariat office of the DPRD district of Probolinggo city. In this study the hypothesis put forward is